Criminal Responsibility of Public Accountant to Tax Crime - Leonardy, Ronald (Universitas Pelita Harapan, 2022)
Criminal Responsibility of Public Accountant regarding to the Law Number 5 of 2011 based on malicious to benefiting own self or specific party unlawfully. Meanwhile regarding to General Provisions and Tax Procedures (KUP) criminal responsibility of Public Accountant based on subjective fault in form of negligence or deliberately which cause losses to the revenues of the state. The difference base of criminal responsibility rise conflict against law enforcement of tax crime resulting Public Accountant become free or burdened with criminal responsibility. Through normative law research, the problem assessed to discover the ideal regulation for criminal responsibility of Public Accountant on tax crime with taking attention aspects of justice, benefit, and legal certainty. The research which performed with regulations approach conclude that objective fault is become ideal base of criminal responsibility for Public Accountant which having own characteristic profession. Objective fault is not determined by inner connection between the man with his act, but have firm and clear measurement. Beside that, jointly responsibility also can be combination factor for criminal responsibility base of Public Accountant on tax crime. With jointly responsibility make Public Accountant have opportunity to participate in recover losses to revenues of the state caused by tax crime. Thus, the revenues of the states which become main objectives will more guaranteed.